Flow pattern analysis in type B aortic dissection patients after stent‐grafting repair: Comparison between complete and incomplete false lumen thrombosis. (5th March 2018) - Wan Ab Naim, Wan Naimah; Ganesan, Poo Balan; Sun, Zhonghua; Lei, Jing; Jansen, Shirley; Hashim, Shahrul Amry; Ho, Teik Kok; Lim, Einly
Abstract: Endovascular stent graft repair has become a common treatment for complicated Stanford type B aortic dissection to restore true lumen flow and induce false lumen thrombosis. Using computational fluid dynamics, this study reports the differences in flow patterns and wall shear stress distribution in complicated Stanford type B aortic dissection patients after endovascular stent graft repair. Five patients were included in this study: 2 have more than 80% false lumen thrombosis (group 1), while 3 others had less than 80% false lumen thrombosis (group 2) within 1 year following endovascular repair. Group 1 patients had concentrated re‐entry tears around the abdominal branches only, while group 2 patients had re‐entry tears that spread along the dissection line. Blood flow inside the false lumen which affected thrombus formation increased with the number of re‐entry tears and when only small amounts of blood that entered the false lumen exited through the branches. In those cases where dissection extended below the abdominal branches (group 2), patients with fewer re‐entry tears and longer distance between the tears had low wall shear stress contributing to thrombosis. This work provides an insight into predicting the development of complete or incomplete false lumen thrombosis and has implications for patient selection for treatment. Abstract : Patients having more than 80% false lumen thrombosis had concentrated re‐entry tears around the abdominal branches, while patients with less than 80% thrombosis had re‐entry tears that spread along the dissection line. Patients with fewer re‐entry tears and longer distance between the tears had thrombosis in between tears. Blood flow inside the false lumen increased with the number of re‐entry tears and when only small amounts of blood that entered the false lumen exited through the branches.